PENGENALAN APLIKASI CANVA KEPADA MASYARAKAT DAN STAF PEMERINTAHAN DESA SIDOSARI LAMPUNG SELATAN - Novia Utami Putri (Universitas Teknokrat Indonesia, 2022)
The design of a product or logo is very important for entrepreneurs in their umkm or businesses that are involved in the community. Design can also make a village government famous through social media, therefore we carry out design training which will later be useful for people who have an effort to promote through a good and attractive design work. Primarily this design is intended for staff or village government training at the kominfo section in Sidosari village, South Lampung. To increase the existence of the village government.